Imaging deposition-dependent supramolecular chiral organisation. Issue 28 (17th March 2022) - Killalea, C. Elizabeth; Samperi, Mario; Siligardi, Giuliano; Amabilino, David B.
Abstract : Chiral diketopyrrolopyrrole thin films imaged with spatially-defined Mueller Matrix Polarimetry revealed different supramolecular homogeneity for spun-coated and drop-coated films, indiscernible with absorption spectroscopy or optical microscopy. Abstract : Thin films of a chiral diketopyrrolopyrrole derivative were imaged with spatially-defined Mueller Matrix Polarimetry, focussing on the Circular Dichroism signal, giving unique insight into the impact that deposition techniques and thermal annealing can have on chiral supramolecular structures in the solid state, where homogeneity was observed for spun-coated films while drop-coating afforded chiroptical diversity in the material, a feature invisible to absorption spectroscopy or optical microscopy.